Analysis of biodiesel process from waste cooking oil using heterogeneous catalyst field snail shell (pila ampullacea) - Ridho, Ainur Rosyid; Prasetyo, Dafit Ari; Susmiati, Yuana; Ulma, Zeni (Politeknik Negeri Lhokseumawe, 2024)
Biodiesel is an alternative fuel in the form of Fatty Acid Methyl Ester (FAME) which can be renewed using vegetable oils and animal oils through esterification or transesterification processes. This study used waste cooking oil as a raw material for biodiesel with a CaO catalyst from the shells of field snails (Pila ampullacea) which were calcined for 4 hours at a temperature of 700°C. This experiment aim to study of the effect of temperature (55°C, 60°C, 65°C) and catalyst weight (4%, 6%, 8%), for 2 hours the transesterification process and the molar ratio of oil to methanol was 1:9. Crude Biodiesel from the transesterification process washed using dry washing method with activated coconut shell charcoal which has been activated using 1M H3PO4. Based on this research, the optimum yields about 91,5%-volume, were obtained in A2T2 with temperature 60°C and a catalyst weight of 6% with a biodiesel yield of 91.5%. The characteristics of the biodiesel produced were kinematic viscosity 3.32 cSt, density 863 Kg/m3, acid number 0.543%, iodine number 14.3%-mass, methyl ester content 169.12% and cetane number 43.28%-mass.